The Impact of Airport Facilities on Non-Aeronautical Revenue Through Airport Traffic And Aeronautical Revenue As Mediating Variables - Handayani, Sri; ., Firmansyah; Oktavilia, Shanty; Dwi Wishnuwardhani , Fadjar (KnE Social Sciences, 2023)
Airport revenue, which consists of aeronautical and non-aeronautical revenue, is very important for airport operations and expansions. Once built, an airport must earn sufficient revenue to cover operating expenses and pay back infrastructure development capital from both public and private sources. Airport facilities and airport traffic determine revenue. The study aimed to analyze the impact of airport facilities on non-aeronautical revenue with airport traffic and aeronautical revenue as mediating variables. The research used a quantitative approach, where the population was Indonesian airports and the samples taken were from 27 Indonesian international airports and 8 Indonesian domestic airports in 2020. The result of this study discovered that non-aeronautical revenue at Indonesian airports can be affected directly and indirectly by airport facilities, airport traffic and aeronautical revenue. Airport facilities had a positive and significant direct effect on airport traffic. Airport traffic had a positive and significant direct effect on aeronautical revenue. Aeronautical revenue had a positive and significant direct effect to the Non-Aeronautical Revenue. However, only airport traffic had an indirect and significant effect on non-aeronautical revenue with aeronautical revenue as the mediating variable. Keywords: Airport Facilities, Airport Traffic, Airport Revenues, Aeronautical Revenue, Non-Aeronautical Revenue